2001
DOI: 10.1128/jvi.75.19.9493-9501.2001
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Type 2-Mediated Transduction of Human Monocyte-Derived Dendritic Cells: Implications for Ex Vivo Immunotherapy

Abstract: Dendritic cells (DCs) are pivotal antigen-presenting cells for regulating immune responses. A major focus of contemporary vaccine research is the genetic modification of DCs to express antigens or immunomodulatory molecules, utilizing a variety of viral and nonviral vectors, to induce antigen-specific immune responses that ameliorate disease states as diverse as malignancy, infection, autoimmunity, and allergy. The present study has evaluated adeno-associated virus (AAV) type 2 as a vector for ex vivo gene tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 54 publications
2
51
0
Order By: Relevance
“…[4][5][6] In addition, potential applications of AAV as a vector for immunotherapy of infectious diseases and cancer are being developed. 2,7,8,10,12 Although most of the preclinical studies and clinical trials so far have utilized serotype 2 AAV vectors, recent studies suggest that alternate serotype vectors with different host cell receptor specificity could have better utility for gene transfer to rAAV2 refractory target cells. [16][17][18][19] One of the cell types that shows poor transduction efficiency for rAAV2 is DC, mouse DC in particular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] In addition, potential applications of AAV as a vector for immunotherapy of infectious diseases and cancer are being developed. 2,7,8,10,12 Although most of the preclinical studies and clinical trials so far have utilized serotype 2 AAV vectors, recent studies suggest that alternate serotype vectors with different host cell receptor specificity could have better utility for gene transfer to rAAV2 refractory target cells. [16][17][18][19] One of the cell types that shows poor transduction efficiency for rAAV2 is DC, mouse DC in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies of human peripheral blood monocyte-derived DC indicated varying efficiency of AAV2 transduction. 12 Other preclinical studies of the application of rAAV to DC-based immunotherapies have also been limited by poor transduction efficiency of DC by serotype 2 vectors. [13][14][15] Alternate serotype vectors with different host cell receptor specificity have increased the repertoire of AAV available for gene therapy applications.…”
Section: Introductionmentioning
confidence: 99%
“…59 Whether immature DCs take up rAAV vectors via a receptor-mediated uptake remains to be determined considering the high phagocytic activity of this cell population. In summary, the current working hypothesis is that rAAV is incapable of recruiting immature APC in high enough numbers to the site of vector administration resulting in lack of T-cell activation and long-term gene transfer as described in many studies utilizing this vector platform.…”
Section: Interaction Of Aav With Dcsmentioning
confidence: 99%
“…However, only limited success has been obtained to date. One of the major obstacles in delivering therapeutic genes into human MDM is the poor transduction efficiency under most currently available gene-transfer conditions [8,26,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%